2020
DOI: 10.2174/1871530320666200813135905
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Peripheral Blood Cells and the Frailty Syndrome in Patients with Cardiovascular Diseases

Abstract: Background: Frailty syndrome is characterized by multisystem dysregulation frequently found in older individuals or even in younger patients with chronic disabling diseases such as cardiovascular diseases. Objective: To determine whether peripheral blood cell count, and its subpopulations, red blood cell and platelets, morphology and different ratios (neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and red blood distribution width-to-platelet ratio) are associated with cardiac frail patients, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In order to enhance knowledge of the cellular bases of the inflammatory state associated with frailty, four studies have explored the association between frailty and the neutrophil/lymphocyte ratio (NLR) [ 21 , 25 , 26 , 29 ], which is a more accurate marker of inflammation than the individual lymphocyte count, since it reflects the balance between two cellular markers of inflammation [ 36 ]. In a study carried out in cancer patients, the NLR was positively correlated with frailty, evaluated using the Carolina frailty index of 36 items [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to enhance knowledge of the cellular bases of the inflammatory state associated with frailty, four studies have explored the association between frailty and the neutrophil/lymphocyte ratio (NLR) [ 21 , 25 , 26 , 29 ], which is a more accurate marker of inflammation than the individual lymphocyte count, since it reflects the balance between two cellular markers of inflammation [ 36 ]. In a study carried out in cancer patients, the NLR was positively correlated with frailty, evaluated using the Carolina frailty index of 36 items [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In specific terms, they observed that an increase in NLR results in an increased risk of frailty. Another study found a higher NLR in frail patients with cardiovascular disease [ 26 ]. Although this marker of inflammation has not been studied in the general population of older adults, in a study carried out by Fernández-Garrido et al [ 32 ] in institutionalized older women, the neutrophil and lymphocyte percentages were correlated with the frailty phenotype score in opposite directions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations